2012
DOI: 10.1111/j.1471-0528.2011.03268.x
|View full text |Cite
|
Sign up to set email alerts
|

Classification of episiotomy: towards a standardisation of terminology

Abstract: Seven episiotomy incisions are described in the literature, although only midline, mediolateral or lateral episiotomies are commonly used. Recent research has demonstrated variations in both site and direction of the incision, and differences between the angle of incision at the time of crowning of the fetal head and the angle of the scar once the wound has been repaired. We review this evidence and suggest that this variation may undermine the reliability of much published work. We suggest a standardised defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 43 publications
1
99
0
9
Order By: Relevance
“…Active second stage of labour was defined as commencement of active pushing until birth of the infant. The exclusive practice in Finland is of lateral episiotomy type [11], contrasting with more common use of mediolateral or midline episiotomy in other parts of the world.…”
Section: Methodsmentioning
confidence: 99%
“…Active second stage of labour was defined as commencement of active pushing until birth of the infant. The exclusive practice in Finland is of lateral episiotomy type [11], contrasting with more common use of mediolateral or midline episiotomy in other parts of the world.…”
Section: Methodsmentioning
confidence: 99%
“…While some authors have defined mediolateral episiotomies as those at 60°at the time of cutting [68,69], others have suggested an angle of >30°from the midline as the criterion [70]. The problem with these definitions is that there was no accurate way of measuring these angles.…”
Section: Angle Of the Episiotomymentioning
confidence: 99%
“…Lateral episiotomy, the exclusive episiotomy technique practiced in Finland, is when an incision is made to the vaginal introitus 1 or 2 cm lateral to the midline and directed towards the ischial tuberosity 10. Our previous work demonstrated that lateral episiotomy was associated with a lower OASIS incidence in first births and a higher rate in second and subsequent births,11 but use of episiotomy had declined substantially over the decade to 2007 among both women with first vaginal births and multiparous women as the incidence of OASIS increased 12.…”
Section: Introductionmentioning
confidence: 99%